COMPARATIVE ANALYSIS OF SLOVENIAN AND RUSSIAN POLITICAL DISCOURSE (Philological Studies, 2019)
Words are not solely means for expressing ideas but communication means for establishing meanings and reaching common goals as well. Politics is a language game, where the language is used to notify public of political affairs. That is also the reason we have to focus on the way the language is used. This paper is based mostly on theoretical frame of pragmatic linguistics. It focuses on the analysis of language use in political environment. I focus also on the meaning and syntax. As a case study, I use examples of Slovenian and Russian political discourse.
Keywords: language, political discourse, political activity